How to Develop Oral Communication Skill of Junior High School Students: The Experience of a Good EFL Teacher - Marcellina, Nadya; Setyono, Budi; Tasnim, Zakiyah (English Education Study Program, 2022)
As Covid-19 pandemic has caused the closure of schools for a long period of time, English teaching and learning process must be conducted online. To know how English teachers conducted online teaching, the present study investigated the experiences of a good EFL teacher in using different kinds of strategies to develop Junior High School students’ oral communication skill. Using a narrative research design, data were collected from semi-structured interview with a Junior High School English teacher using purposeful sampling to provide rich information to answer research question. The results of the thematic analysis showed a big theme that emerged, i.e., strategies to develop the students’ oral communication skill. This big theme is divided into four sub-themes: strategies to develop the students’ dialogue skill, strategies to develop the students’ monologue skill, strategies to develop the students’ fluency, strategies to develop the students’ accuracy. In addition, the results of this research are expected to give meaningful contribution, not only for the other English teachers but also for the other researchers.